2020
DOI: 10.38079/igusabder.784094
|View full text |Cite
|
Sign up to set email alerts
|

Çalışma Hayatındaki Bireylerin Probiyotik Besinler Hakkındaki Bilgi Düzeyi ve Tüketim Durumlarının Belirlenmesi

Abstract: Son yıllarda yapılan çalışmalar probiyotiklerin sağlık üzerine olan etkilerini göstermekle beraber, bireylerin probiyotik bilgi düzeyi arttıkça tüketimin de arttığı gözlemlenmiştir. Bu Özgün Araştırma Makalesi (Original Research Article) Geliş /

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…It was observed that adults chose the option "Probiotics can be used for weight loss" and "Probiotics can be used together with antibiotics" at lower rates. 27 Similar to the results of this study, it is seen in other studies in the literature that current developments related to probiotics are not sufficiently understood.…”
Section: Discussionsupporting
confidence: 72%
“…It was observed that adults chose the option "Probiotics can be used for weight loss" and "Probiotics can be used together with antibiotics" at lower rates. 27 Similar to the results of this study, it is seen in other studies in the literature that current developments related to probiotics are not sufficiently understood.…”
Section: Discussionsupporting
confidence: 72%